Pityriasis versicolor: insight into current knowledge and treatment possibilities - Jakub Parys; Agnieszka Mikosińska; Martyna Kaźmierczak; Patrycja Kałuziak; Maciej Mossakowski; Marta Jajczak; Aleksandra Witek; Stanisław Jesionek; Mateusz Litwin (Journal of Education, Health and Sport)
Background: Pityriasis versicolor is a prevalent superficial mycosis caused by saprophytic yeasts of the Malassezia genus. It primarily affects adolescents and young adults, presenting as hypo- or hyperpigmented macules on the skin, commonly located on the trunk and upper arms. While various topical and systemic antifungal treatments are available, high relapse rates remain a significant clinical challenge. The condition often leads to psychological distress due to visible lesions on the skin surface.